What to read when : the books and stories to read with your child and all the best times to read them - Allyn, Pam, 1963- (Avery, 2009)
"Award-winning educator Allyn offers parents and caregivers essential advice on choosing appropriate titles for their children--taking into account a child's age, attention ability, gender, and interests--along with techniques for reading aloud effectively."